Production Ethics of Muslim Batik Entrepreneurs in Pekalongan - Muhammad Izza; Tarmidzi, Tarmidzi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This research aims to find out the influence of ethics in batik (Indonesian traditional dyeing designs in clothing) production of Muslim entrepreneurs with their environment in Pekalongan, Central Java. The urgency is that the production ethics have a close relationship with waste and environment. This study used primary data from questionnaires filled by Muslim batik entrepreneurs. The OLS method was applied to analyze the total of 30 samples using SPSS. In this analysis, there were two things having strong significant correlations to production ethics namely (1) the application of Islamic values of the entrepreneurs on environmental sustainability and (2) the acknowledgement of the entrepreneurs regarding to the counseling of batik waste from local government.